The effectiveness of integrating interactive technology in reading comprehension: A case study of Jamaica's grade school - Iyare, Ngozi F.; James, Julia; Amonde, Tom M. (Journal of Information Technology Education: Research, 2018)
Aim/Purpose: There is growing number of countries embarking on large-scale, government-supported initiatives (e.g., Antigua & Barbuda, Australia, Brazil, India, Iran, Jamaica, Kazakhstan, Pakistan, Russia, Turkey, and the United Arab Emirates) to distribute tablet devices to students in the K-12 schooling sector. The review of the government-supported initiatives concluded that the majority of these initiatives have been driven not by educational frameworks or research-based evidence but by the tablet hype. The goal of this study is to provide research-based evidence by investigating if the learning experience for grade-three learners with interactive technology improves knowledge and skills in reading comprehension compared to learning in the traditional chalk and talk environment. Background: Prior studies provided limited evidence based mainly on data from developed countries about the influence of the use of interactive technology on reading comprehension at lower grade school level. Methodology: Employing a mixed-method case study research approach, this study aims to investigate the effects of integrating interactive technology in reading comprehension and examine the perspectives of students. This case study employed a sample of 30 public school third-grade students located in a relatively poor residential area in St Catherine, Jamaica as well as the two classroom teachers. Thirty students were divided into two groups – an experimental group, which included 16 participants and a control group, which included 14 participants. The intervention program was carried out over a period of eight weeks. Contribution: This study has provided (a) additional data to show evidence for the effectiveness of interactive technology in reading comprehension and (b)research based evidence for the distribution of computer devices to students in the K-12 schooling sectors. Findings: We found empirical support for the positive effects of technology-based approaches for addressing reading comprehension and vocabulary skills. Our results were based on the pre-test and post-test assessments. Additional data was collected using a survey questionnaire which was given to the students before and after the intervention. The change from pretest to posttest was significantly different between the two groups as measured by the Mann Whitney U test. Recommendations for Practitioners: The empirical support for the effects of technology-based approaches for addressing reading comprehension and vocabulary skills identified in this study will assist teachers with strategies and programs that should improve students' motivation as well as their grades. Recommendation for Researchers: For future studies, we recommend focusing on a longer intervention period and using a larger sample size that would likely yield more definitive and generalizable results.
Publisher: Informing Science Institute, 131 Brookhill Court, Santa Rosa, CA 95409 KerkoCite.ItemAlsoKnownAs: 10.28945/4098 2339240:D393J5PP 2405685:57ZK2DLD 2534378:8J9G8HNR 2534378:CCG5NKEW
Keywords: Case Studies; Control Groups; Conventional Instruction; ERIC; Current Index to Journals in Education (CIJE); Elementary Education; Elementary School Students; Experimental Groups; Foreign Countries; Grade 3; Instructional Effectiveness; Jamaica; Mastery Learning; Outcomes of Education; Reading Comprehension; Reading Improvement; Reading Instruction; Teaching Methods; Technology Integration

Synergies Between the Principles for Digital Development and Four Case Studies - Haßler, Björn; Broadbent, E.; Cunningham, A.; Chimombo, J.; Jamil, B. R.; Kauthria, R.; Lake, L.; Rose, P.; Sarfraz, S.; Szekely, M. (Research for Equitable Access and Learning (REAL) Centre, Faculty of Education, University of Cambridge, 2018)
This report was prepared by Bjöern Haßler for the Research for Equitable Access and Learning (REAL) Centre, University of Cambridge, UK, with support from the Global Education & Skills Forum (GESF) Alliance on Assessment and Impact for Learning. This Alliance was co-chaired by Pauline Rose (REAL Centre, University of Cambridge, United Kingdom) and Baela Raza Jamil (Idara-e-Taleem-o-Agahi, Pakistan) and included the following members: Emma Broadbent (The Varkey Foundation, United Kingdom), Andrew Cunningham (Aga Khan Foundation, Switzerland), Joseph Chimombo (Ministry of Education, Malawi), Rashmi Kauthria (Global Teacher Prize Finalist 2017, India), Lucy Lake (Camfed, United Kingdom), Shajia Sarfraz (Independent Researcher, Pakistan) and Miguel Szekely (Center for Education and Social Studies, Mexico).
shortDOI: 10/ghgngb KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1196830 10.5281/zenodo.1219919 10/ghgnf9 10/ghgngb 1867969:MS4YEFUV 2129771:3HPEHK45 2339240:6UEQFTXM 2339240:HYX3RTJZ 2339240:WNVALD7D 2405685:A8G2S2ZT 2405685:FUKJ5SE8 2405685:IGGQMIXI 2405685:PWCIYQJM
Keywords: _DOILIVE; ___working_potential_duplicate; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Learning through Video Games: A Case Study of Private Schools of Pakistan - Khalid, Tooba; Batool, Syeda Hina (Ieee, 2018)
This study investigated video game based academic and information literacy (IL) learning of teenagers of private schools of Lahore city. Lahore is one of the big city and knowledge hub of Pakistan. Previous literature highlighted the importance of video games in learning academic and IL skills; therefore, the present study aims to reveal this fact in local context. The presented study adopted qualitative research approach and utilized phenomenological research method to achieve its objectives. The data was collected through interviews. The study participants were teenagers (13 to 19 years) of elite economic class private schools who were frequent video game players. Based on the study findings, it can be concluded that playing video games has positive impact on teenagers' learning. The majority of the participants were of view that challenges of completing various stages of games and interacting with online competitors enhanced their social (communication) and information literacy (searching/locating and evaluating) skills. The results of the study are benefitted for the game developers, teachers, librarians and parents.
Pages: 135-139 Publication Title: 2018 International Conference on Information Management and Processing (icimp 2018) WOS:000458552800025 KerkoCite.ItemAlsoKnownAs: 2339240:N7BHL93X 2405685:HSIXBVLD
Keywords: Pakistan; academic learning; information literacy; learning; skills; video games

Advancing women’s digital skills and economic empowerment through girls in tech Indonesia: A case study - Afiani, Isyfi (Salasika, 2018)
The advancing Information and Communication Technology (ICT) has massively supported the economy in the digital era as it disseminates, stores, brings added value and manages information to provide unlimited opportunities for economic development. However, ICT may contribute to discrimination and existing inequalities reinforcement so-called the digital divide. Since all aspects of human interaction with ICT are gendered, this study tackles the digital gender divide issue, that is, the gap between men and women regarding access to, content and use of ICT. Accordingly, in 2016, the gender gap of global internet users was 12% and it grows every year. In response to this condition, a global movement promoting women engagement in ICT has emerged. This study, therefore, depicts the role of Girls in Tech Indonesia community as a chapter of Global Girls in Tech movement in advancing women economic empowerment through ICT by implementing transformational leadership concepts and Longwe’s empowerment framework. In the core of qualitative studies, this study shows that Girls in Tech Indonesia’s leadership performance contributes positively to women empowerment.
1 citations (Crossref) [2024-04-29] Number: 1 KerkoCite.ItemAlsoKnownAs: 10.36625/sj.v1i1.39 2339240:E5W3KXKL 2405685:7PTB86S9
Keywords: Empowerment; Girls in Tech; ICT; Leadership; ⛔ No INSPIRE recid found

Synergies Between the Principles for Digital Development and Four Case Studies - Haßler, Björn; Broadbent, E.; Cunningham, A.; Chimombo, J.; Jamil, B. R.; Kauthria, R.; Lake, L.; Rose, P.; Sarfraz, S.; Szekely, M. (Research for Equitable Access and Learning (REAL) Centre, Faculty of Education, University of Cambridge, 2018)
This report was prepared by Bjöern Haßler for the Research for Equitable Access and Learning (REAL) Centre, University of Cambridge, UK, with support from the Global Education & Skills Forum (GESF) Alliance on Assessment and Impact for Learning. This Alliance was co-chaired by Pauline Rose (REAL Centre, University of Cambridge, United Kingdom) and Baela Raza Jamil (Idara-e-Taleem-o-Agahi, Pakistan) and included the following members: Emma Broadbent (The Varkey Foundation, United Kingdom), Andrew Cunningham (Aga Khan Foundation, Switzerland), Joseph Chimombo (Ministry of Education, Malawi), Rashmi Kauthria (Global Teacher Prize Finalist 2017, India), Lucy Lake (Camfed, United Kingdom), Shajia Sarfraz (Independent Researcher, Pakistan) and Miguel Szekely (Center for Education and Social Studies, Mexico).
Keywords: _DOILIVE; ___working_potential_duplicate; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Synergies Between the Principles for Digital Development and Four Case Studies - Haßler, Björn; Broadbent, E.; Cunningham, A.; Chimombo, J.; Jamil, B. R.; Kauthria, R.; Lake, L.; Rose, P.; Sarfraz, S.; Szekely, M. (Research for Equitable Access and Learning (REAL) Centre, Faculty of Education, University of Cambridge, 2018)
This report was prepared by Bjöern Haßler for the Research for Equitable Access and Learning (REAL) Centre, University of Cambridge, UK, with support from the Global Education & Skills Forum (GESF) Alliance on Assessment and Impact for Learning. This Alliance was co-chaired by Pauline Rose (REAL Centre, University of Cambridge, United Kingdom) and Baela Raza Jamil (Idara-e-Taleem-o-Agahi, Pakistan) and included the following members: Emma Broadbent (The Varkey Foundation, United Kingdom), Andrew Cunningham (Aga Khan Foundation, Switzerland), Joseph Chimombo (Ministry of Education, Malawi), Rashmi Kauthria (Global Teacher Prize Finalist 2017, India), Lucy Lake (Camfed, United Kingdom), Shajia Sarfraz (Independent Researcher, Pakistan) and Miguel Szekely (Center for Education and Social Studies, Mexico).
Keywords: _DOILIVE; ___working_potential_duplicate; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

#CostingEquity: The case for disability-responsive education financing - Myers, Juliette; Pinnock, Helen; Baboo, Nafisa; Lewis, Ingrid (International Disability and Development Consortium, 2018)
The #CostingEquity research project investigated the benefits of financing disability-inclusive education, the current state of education financing with regard to inclusion, and what needs to change in order for education financing to effectively support the realisation of SDG 4. The #CostingEquity research report addresses three broad questions: • How do international donors and domestic governments currently fund disability-inclusive education? • What are the gaps and challenges in financing disability-inclusive education? • What needs to change to increase quality, equitable financing for learners with disabilities? The report aims to contribute to a better understanding of the issues related to equitable financing for education for learners with disabilities. It considers additional marginalising factors such as gender, socio-economic status, social circumstances and urban/rural location. It offers key arguments for civil society activists, donors and government advisors to make the case for building and strengthening inclusive education systems. Detailed case studies provide useful examples of financing gaps, challenges and promising practice from developing country contexts, major education donors, and new and emerging philanthropic donor foundations. The focus of case studies and examples is on low and lower-middle income countries and were chosen to reflect a broad range of regions and countries.The report concludes with a series of recommendations for domestic and external financing approaches.
KerkoCite.ItemAlsoKnownAs: 2339240:3XWFXVAP 2339240:DU3DQXWC 2405685:9WX2Z28W 2405685:EQP34VAJ

Using online peer assessment in an instructional technology and material design course through social media - Demir, Mehmet (Higher Education: The International Journal of Higher Education Research, 2018)
This study was designed to investigate the student teachers perceptions about and benefits and challenges of using Facebook as an online peer assessment tool for the student teachers' works. The study group included 24 student teachers in science education department of a state university located in the southeast region of Turkey. A case study approach of the qualitative method was employed in the research. Semi-structured interviews were conducted to collect the data. The interviews were audio recorded, and records of all the interviews were transcribed into full text in Turkish. Collected data were analyzed using an emergent coding approach. Codes, then, were categorized to constitute themes and subthemes. The findings indicated that the student teachers were able to give objective feedback on their peers' work and engaged more actively in class after participating in online peer assessment. Additionally, the students found it exciting and productive to use Facebook as a peer assessment tool in their learning.
Publisher: Springer, 233 Spring Street, New York, NY 10013 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2013524252?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1007/s10734-017-0146-9 2339240:I42X9GJR 2405685:9QLMMRGN 2534378:G3WM932R 2534378:Q94E3FCI 2534378:YRDI45P7
Keywords: Case Studies; Case studies; Coding; College students; Computer Uses in Education; ERIC; Current Index to Journals in Education (CIJE); Education–Higher Education; Educational Technology; Educational technology; Feedback; Feedback (Response); Foreign Countries; Higher Education; Higher education; Instructional Technology and Material Design; Internet; Interviews; Learner Engagement; Learning; Mass media; Peer Evaluation; Peer assessment; Peers; Preservice Teachers; Qualitative Research; Qualitative research; Science education; Semi Structured Interviews; Social Media; Social classes; Social media; Social networks; Structured interviews; Student Attitudes; Student teachers; Students; Teachers; Technology; Turkey; __:import:01; __:match:final; __:matched; __:study_id:2097831; __finaldtb

An Investigation into Implementation of ICT in ECD and Primary Schools, in the Light of Free Laptops at Primary One: a case study of teachers implementing ICT into their teaching practice - Tonui, Betty C.; Kerich, E.; Koross, R.; J, K.; Moi, Too (2018)
Information and communication technologies (ICTs) have been touted as being potentially powerful tools that can be used to facilitate the implied educational change and reform. Implementation of ICT in higher education learning environments is a complex task. Teachers and students, but also management, administration and ICT support are affected by and affect the implementation. To facilitate the change processes better the first step is to actually understand what problems and challenges implementation of ICT leads to and how it affects practice. Although classical instructional methods will continue to be used in the teaching-learning process, it is also true that Information Communication Technologies (ICTs) can be harnessed to become powerful pedagogical tools. Proceeding from the premise that there are many ways to use new technologies for teaching and learning, the paper presents literature on the possibilities and challenges of integrating ICT into teaching-learning, the rationale for adopting and using ICTs for learning-teaching, as well as the key factors that influence the adoption and use of ICTs in teaching and learning both from a general perspective and in a technical education context. The paper then outlines and discusses findings of a study designed to investigate the possibilities and challenges of using Information Communication Technology (ICT) in teaching-learning procedures in primary school institutions in Kenya using data obtained from a Tinderet District school in the Rift valley
KerkoCite.ItemAlsoKnownAs: 2339240:CHUK8BFL 2405685:CD7SSBUP

Mathematical modelling in teacher education: dealing with institutional constraints - Barquero, Berta; Bosch, Marianna; Romo, Avenilde (ZDM: The International Journal on Mathematics Education, 2018)
Considering the general problem of integrating mathematical modelling into current educational systems, this paper focuses on the "ecological dimension" of this problem–the institutional constraints that hinder the development of mathematical modelling as a normalised teaching activity–and the inevitable step of the professional development of teachers. Within the framework of the Anthropological Theory of the Didactic, this step is approached using the "study and research paths for teacher education" (SRP-TE), an inquiry-based process combining practical and theoretical questioning of school mathematical activities. We present a research study focusing on the design and analysis of an online and distance-learning course for in-service mathematics teachers based on the SRP-TE methodology. This course starts from the initial question of how to analyse, adapt and integrate a learning process related to mathematical modelling and how to sustain its long-term development. Our analysis is based on a case study consisting in four successive editions of a course for Latin American in-service mathematics teachers held at the Centre for Applied Research in Advanced Science and Technology in Mexico. The starting point is a modelling activity about forecasting the number of Facebook users, which includes functional modelling and regression. The results show how the course represents a valuable instrument to help teachers progress in the critical issue of identifying institutional constraints–most of them beyond the scope of action of teachers and students and not approached by previous research–hindering the integration of mathematical modelling in current secondary schools.
Publisher: Springer, 233 Spring Street, New York, NY 10013 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2101593199?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1007/s11858-017-0907-z 2339240:4YXECT54 2405685:2GGB99HT 2405685:6B4BREQ8 2534378:8BWRCH2S 2534378:RTGC7399
Keywords: Anthropological theory of the didactic; Barriers; Case Studies; Distance Education; ERIC; Current Index to Journals in Education (CIJE); Ecological Factors; Ecology; Foreign Countries; Functions; Inservice Teacher Education; Institutional constraints; Instructional Design; Mathematical Models; Mathematical modelling; Mathematics Teachers; Mexico; Online Courses; Prediction; Regression (Statistics); Social Media; Study and research path; Teacher education; __:import:01; __:match:final; __:matched; __:study_id:2095891; __finaldtb

Synergies between the principles for digital development and four case studies - Haßler, Bjoern (REAL Centre, Faculty of Education, University of Cambridge, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:NGZHXKD5 2405685:C4X9KNTW
Keywords: ___working_potential_duplicate

Synergies Between the Principles for Digital Development and Four Case Studies - Haßler, Björn; Broadbent, E.; Cunningham, A.; Chimombo, J.; Jamil, B. R.; Kauthria, R.; Lake, L.; Rose, P.; Sarfraz, S.; Szekely, M. (Research for Equitable Access and Learning (REAL) Centre, Faculty of Education, University of Cambridge, 2018)
KerkoCite.ItemAlsoKnownAs: 2405685:IG2SDM9M 2486141:SKVSDTSW

Online tools supporting the conduct and reporting of systematic reviews and systematic maps: a case study on CADIMA and review of existing tools - Kohl, Christian; McIntosh, Emma J.; Unger, Stefan; Haddaway, Neal R.; Kecke, Steffen; Schiemann, Joachim; Wilhelm, Ralf (Environmental Evidence, 2018)
Systematic reviews and systematic maps represent powerful tools to identify, collect, evaluate and summarise primary research pertinent to a specific research question or topic in a highly standardised and reproducible manner. Even though they are seen as the “gold standard” when synthesising primary research, systematic reviews and maps are typically resource-intensive and complex activities. Thus, managing the conduct and reporting of such reviews can become a time consuming and challenging task. This paper introduces the open access online tool CADIMA, which was developed through a collaboration between the Julius Kühn-Institut and the Collaboration for Environmental Evidence, in order to increase the efficiency of the evidence synthesis process and facilitate reporting of all activities to maximise methodological rigour. Furthermore, we analyse how CADIMA compares with other available tools by providing a comprehensive summary of existing software designed for the purposes of systematic review management. We show that CADIMA is the only available open access tool that is designed to: (1) assist throughout the systematic review/map process; (2) be suited to reviews broader than medical sciences; (3) allow for offline data extraction; and, (4) support working as a review team.
KerkoCite.ItemAlsoKnownAs: 10.1186/s13750-018-0115-5 2405685:7WGMZPAG 2486141:PBSSCM7N 2486141:WI9XD8XN
Keywords: Evidence synthesis; Managing systems; Rapid review; Review management; Systematic review software; Text mining; Time management; _Added-ailr-2024

Enhancing social inclusion through innovative mobile learning in Uruguay: case study by the UNESCO-Fazheng project on best practices in mobile learning - UNESCO Biblioteca Digital - UNESCO (2018)
KerkoCite.ItemAlsoKnownAs: 2339240:XAJJS9ZC 2405685:WU8A4HM4

Education, poverty and "purity" in the context of adolescent girls' secondary school retention and dropout: A qualitative study from Karnataka, southern India - Ramanaik, Satyanarayana; Collumbien, Martine; Prakash, Ravi; Howard-Merrill, Lottie; Thalinja, Raghavendra; Javalkar, Prakash; Murthy, Srikanta; Cislaghi, Ben; Beattie, Tara; Isac, Shajy; Moses, Stephen; Heise, Lori; et al. (PLoS ONE, 2018)
Background Gender-related norms and poverty remain important structural barriers to secondary school attendance among adolescent girls in southern India. We analyse how gender norms interact with family deprivation and dynamics to result in girls dropping out of school; we identify the main facilitators of school retention and changes to gender socialisation. Methods Longitudinal qualitative case studies with 36 girls were nested within a cluster randomized trial to evaluate the Samata intervention targeting adolescent girls in Bagalkote and Vijayapura districts in northern Karnataka. We used two rounds of in-depth interviews, conducted in 2014 at a time when respondents were in 8th standard at the age of 13 to 14 and sixteen months later. We combined thematic and narrative analyses. Results Our study found that poverty and socioeconomic realities at the household level strongly affect conformity with discriminatory gender practices such as restricting girls’ mobility. The value placed on education by parents clearly differentiates the regular school goers from those frequently absent and others who dropped out. With active encouragement of the girls’ educational and career aspirations, parents engendered the girl’s agency to communicate openly both at home and at school, allowing subtle changes to gender performance while resisting the pressure of social sanctions. In contrast, where educational aspirations were weak, parents invested more intensely in enforcing correct performance of gender, prioritising her well-being by aiming to secure her future in a good marriage. Among poorer families, girls’ domestic duties came at the cost of schooling with concerns about protecting her sexual purity predominating. Conclusions In contexts where a strong gender ideology of virginity before marriage rules, subtle shifts in harmful gender practices are possible. Interventions aiming to improve education need to target the most deprived families, focussing on trust building through open communication.
shortDOI: 10/gd6jwg KerkoCite.ItemAlsoKnownAs: 10.1371/journal.pone.0202470 10/gd6jwg 2405685:Z8HRZP6T

Real girls, real lives, connected: A global study of girls’ access and usage of mobile, told through 3000 voices. - Vodafone Foundation (Vodafone Foundation, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:3PIDJ4Q7 2339240:4X6NX5DF 2405685:6IXNFYTS 2405685:HF2CK86W 2405685:V5WB4PZA

The discourse on ICT teacher professional development needs: The case of a South African teachers’ union - Dlamini, Reuben; Mbatha, Khanyisile (International Journal of Education and Development using ICT, 2018)
The prevalence and adoption of Information and Communication Technology (ICT) tools in education has often been guided by utopian perspectives without proper research to understand the schooling context and teachers’ ICT development needs. This paper reports on the findings from a study of in-service teachers who are members of a teachers’ union in South Africa. These teachers were surveyed using a questionnaire based on Second Information Technology in Education Study (SITES), which is an analytic framework that includes teacher characteristics, pedagogical practices and ICT use, school...
Publisher: Open Campus, The University of the West Indies, West Indies KerkoCite.ItemAlsoKnownAs: 2339240:JX8TEHVV 2405685:UB39IXQK
Keywords: ⛔ No DOI found

The discourse on ICT teacher professional development needs: The case of a South African teachers’ union - Dlamini, Reuben; Mbatha, Khanyisile (International Journal of Education and Development using ICT, 2018)
The prevalence and adoption of Information and Communication Technology (ICT) tools in education has often been guided by utopian perspectives without proper research to understand the schooling context and teachers’ ICT development needs. This paper reports on the findings from a study of in-service teachers who are members of a teachers’ union in South Africa. These teachers were surveyed using a questionnaire based on Second Information Technology in Education Study (SITES), which is an analytic framework that includes teacher characteristics, pedagogical practices and ICT use, school...
Publisher: Open Campus, The University of the West Indies, West Indies KerkoCite.ItemAlsoKnownAs: 2339240:JX8TEHVV 2405685:UB39IXQK
Keywords: ⛔ No DOI found

A second chance to dream: initiating ODeL in secondary school re-entry programs for young adult secondary school dropouts the case of Mumias District, Western Kenya - Musita, Richard; Ogange, Betty O.; Lugendo, Dorine (Distance Education, 2018)
The Kenyan education system has very limited re-entry options for learners who drop out before attaining secondary school certificate. It is very difficult to access training and or secure a job that requires at least secondary school education. This study examined the prospects of initiating Open and Distance e-Learning(ODeL) in re-entry programmes into high school for out of school Young Adult Secondary School Dropouts (Y.A.S.S.D). The study focused on the enablers and challenges of initiating ODeL in the secondary school re-entry programmes. An alternative flexible and sustainable community based ODeL model that potentially can address re-entry for the Y.A.S.S.D is proposed. A qualitative phenomenological design was used; focus group discussion and interviews were conducted from a purposeful sample of participants. The study revealed that the potential of ODeL in addressing re-entry into secondary school for Y.A.S.S.D great. Majority of the participants were aware of the existing secondary school re-entry options, however, ODeL appeared new. Despite there being challenges in introducing the ODeL mode of study in secondary school re-entry programmes, it is viable and requires further exploration. The enablers of this mode of study are largely in place to the extent appreciated by participants in the study.
shortDOI: 10/ggdcng KerkoCite.ItemAlsoKnownAs: 10.1080/01587919.2018.1429896 10/ggdcng 2339240:FKXTDETC 2405685:XWRSN3WD
Keywords: Re-entry; dropouts; open distance e-learning

The discourse on ICT teacher professional development needs: The case of a South African teachers’ union - Dlamini, Reuben; Mbatha, Khanyisile (International Journal of Education and Development using Information and Communication Technology (IJEDICT), 2018)
The prevalence and adoption of Information and Communication Technology (ICT) tools in education has often been guided by utopian perspectives without proper research to understand the schooling context and teachers’ ICT development needs. This paper reports on the findings from a study of in-service teachers who are members of a teachers’ union in South Africa. These teachers were surveyed using a questionnaire based on Second Information Technology in Education Study (SITES), which is an analytic framework that includes teacher characteristics, pedagogical practices and ICT use, school factors and system, and other external factors. This exploratory study was conducted within the framework of a teachers’ union to understand members’ preparedness to integrate ICT tools in their teaching practices. Findings indicate the need for in-service professional development activities in the use of ICT for teaching, in teaching in multicultural environments, and in classroom management. Equally important is the role of school management and administration in the adoption and integration of ICT tools in education. In addition, the research provided clear evidence that despite the huge investments into ICT infrastructure by government, inequalities in ICT competencies among teachers remain. The most important conclusion is that the investments being made are politically motivated and that teachers are being side-lined in the decision-making processes and preference given to political visions.
KerkoCite.ItemAlsoKnownAs: 2339240:FCJF68RN 2405685:HQE8MXWS
Keywords: ⛔ No DOI found

Massive Open Online Courses (MOOCs) for Professional Teacher and Teacher Educator Development: A Case of TESSA MOOC in Kenya - Wambugu, Patriciah W. (Universal Journal of Educational Research, 2018)
This study intends to present a bespoke teacher professional development MOOC designed by Teacher Education for Sub-Saharan Africa (TESSA) team that allows MOOCs to become a viable means offering cost-effective, quality professional teacher development. TESSA is a network of teachers and teacher educators, working to improve classroom teaching in Africa. TESSA MOOC is an innovative approach to capacity building for teacher educators and teachers across Africa. The study presents outputs of an evaluation of TESSA MOOC course undertaken by Kenyan teachers and teacher educators. The experiences of the participants were that the TESSA MOOC was a new but interesting, appealing and flexible course. In addition, the participants were able to learn from one another and what they learnt may impact on their pedagogical skills. Key challenges identified include difficulties in downloading of materials due to lack of internet connectivity and use of ICT phobia for learning. MOOCs represent an untapped potential for teacher professional development that can be a cost and resource effective means to deliver quality education to teachers and teacher educators. Therefore, the teachers and teacher educators may need to exploit this learner based TESSA MOOC to build capacity for teaching.
Publisher: Horizon Research Publishing KerkoCite.ItemAlsoKnownAs: 10.13189/ujer.2018.060604 10/gf622k 2339240:FWBVWVA2 2405685:ARBG7E6A
Keywords: Educational Quality; Faculty Development; Foreign Countries; Information Technology; Online Courses; Teacher Education; Teacher Educators; Teacher Effectiveness

Scaling up successfully: Lessons from Kenya’s Tusome national literacy program - Piper, Benjamin; Destefano, Joseph; Kinyanjui, Esther M.; Ong’ele, Salome (Journal of Educational Change, 2018)
Many successful piloted programs fail when scaled up to a national level. In Kenya, which has a long history of particularly ineffective implementation after successful pilot programs, the Tusome national literacy program—which receives funding from the United States Agency for International Development—is a national-level scale-up of previous literacy and numeracy programs. We applied a scaling framework (Crouch and DeStefano in Doing reform differently: combining rigor and practicality in implementation and evaluation of system reforms. International development group working paper no. 2017-01, RTI International, Research Triangle Park, NC, 2017. https://www.rti.org/publication/doing-reform-differently-combining-rigor-and-practicality-implementation-and-evaluation) to examine whether Tusome’s implementation was rolled out in ways that would enable government structures and officers to respond effectively to the new program. We found that Tusome was able to clarify expectations for implementation and outcomes nationally using benchmarks for Kiswahili and English learning outcomes, and that these expectations were communicated all the way down to the school level. We noted that the essential program inputs were provided fairly consistently, across the nation. In addition, our analyses showed that Kenya developed functional, if simple, accountability and feedback mechanisms to track performance against benchmark expectations. We also established that the Tusome feedback data were utilized to encourage greater levels of instructional support within Kenya’s county level structures for education quality support. The results indicated that several of the key elements for successful scale-up were therefore put in place. However, we also discovered that Tusome failed to fully exploit the available classroom observational data to better target instructional support. In the context of this scaling framework, the Tusome literacy program’s external evaluation results showed program impacts of 0.6–1.0 standard deviations on English and Kiswahili learning outcomes. The program implemented a functional classroom observational feedback system through existing government systems, although usage of those systems varied widely across Kenya. Classroom visits, even if still falling short of the desired rate, were far more frequent, were focused on instructional quality, and included basic feedback and advice to teachers. These findings are promising with respect to the ability of countries facing quality problems to implement a coherent instructional reform through government systems at scale.
shortDOI: 10/gf6298 KerkoCite.ItemAlsoKnownAs: 10.1007/s10833-018-9325-4 10/gf6298 2339240:HUMPM4BM 2339240:LT7INWTK 2339240:PM36I7JC 2339240:S7I52VEN 2339240:YTWJW5GH 2405685:2YJ8XQDL 2405685:NC6R6NWC 2405685:TFDLRYCG 2405685:UXBBCZIX 2405685:VERKPHLS 2405685:X7T5JCV4
Keywords: ___working_potential_duplicate

Interaction in a discussion list: an exploration of cognitive, social, and teaching presence in teachers’ online collaborations - Nami, Fatemeh; Marandi, S Susan; Sotoudehnama, Elaheh (ReCALL: the Journal of EUROCALL, 2018)
Discussion lists have gained a significant popularity in professional development research over the past few decades for the opportunity they provide for asynchronous interaction. This article presents findings from a small-scale case study that aimed at exploring the nature of teachers’ asynchronous exchanges in a discussion list. The data comprised the archived log of the messages in a Yahoo Group discussion list by five in-service English as a foreign language (EFL) teachers who volunteered to take part in a hybrid computer-assisted language learning (CALL) teacher education course in a state university in Iran. The discussion list was incorporated into the course to engage participants in professional dialogue on topics related to technology/CALL. During the initial data analysis, participants’ asynchronous exchanges were grouped as suggestions, questions, unclassified, answers, and delivery, drawing upon Oriogun and Cave’s (2008) SQUAD categorization, following the constant comparative method of analysis. Through a follow-up computer-mediated discourse analysis, cognitive, social, and teaching presence functional moves were identified in the data. Participants used the space not only for socializing and peer instruction but also for constructing knowledge. Despite an uneven pattern of contribution, asynchronous exchanges provided opportunities for knowledge construction at different levels of cognitive presence on topics ranging from technology tools and their affordances/constraints to computer-assisted language testing, materials development, and classroom management. The findings provide CALL teacher education researchers and course designers insights into the potential of asynchronous interaction for online and blended language teacher education.
Place: Cambridge Publisher: Cambridge University Press Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2084810389?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1017/S0958344017000349 2405685:WM42S327 2534378:59HFNMGI 2534378:A5Y5932K 2534378:EEFLCSXC 2534378:G3TW72LP
Keywords: Asynchronous Communication; Blended Learning; CALL teacher education; CASE studies; COMPUTER assisted language instruction; Cognitive processes; Collaborative learning; Colleges & universities; Computer Mediated Communication; Computer assisted instruction–CAI; Computer assisted language learning; Critical thinking; Curriculum development; Data analysis; Discourse Analysis; Distance learning; ERIC; Current Index to Journals in Education (CIJE); Educational Technology; Educational technology; English (Second Language); English as a second language instruction; Faculty Development; Foreign Countries; Foreign languages; Group Discussion; Higher Education; Higher education; Hybrid computers; Interactive learning; Iran; LANGUAGE & languages; Language Teachers; Linguistics–Computer Applications; PROFESSIONAL education; Professional development; School environment; Second Language Instruction; Second language teachers; Social factors; TEACHERS; Teacher Education Programs; Teacher education; Teachers; Teaching; Technology Uses in Education; __:import:01; __:match:final; __:matched; __:study_id:2095858; __finaldtb; asynchronous interaction; cognitive presence; online collaboration; social presence; teaching presence

What have we learned after ten years of systematic reviews in international development? - Waddington, Hugh; Masset, Edoardo; Jimenez, Emmanuel (Journal of Development Effectiveness, 2018)
The paper discusses the role of systematic evidence in helping make better decisions to reach global development targets. Coming at the end of the ﬁrst decade of serious funding and support for systematic evidence generation in development economics and development studies, the paper presents opportunities and challenges for the continued development of systematic review methodologies. It concludes by introducing the papers collected in the issue, which make and demonstrate the case for theory-based approaches to evidence synthesis.
shortDOI: 10/gf5f7j KerkoCite.ItemAlsoKnownAs: 10.1080/19439342.2018.1441166 10/gf5f7j 2339240:NQXMMWG7 2405685:SSJWH27S UA-e9af1e1b-7cd7-4efa-a8ad-391a3c96f523
Keywords: Reviewed

Impact of Education on Labour Market Outcomes in Rural and Urban India - Pradhan, K. C.; Parida, P. C.; Sarangi, Tapas (Reflecting on India’s Development: Employment, Skill and Health, 2018)
This paper examines the returns to education with respect to three labour market outcomes namely wages, employment and occupation using the National Sample Survey Office (NSSO) 68th round (2011–12) data. Wage equation (without selection bias) results point to the fact that returns to education increase at an increasing rate as the level of education increases and the impact of education is found relatively higher in the case of urban than rural areas. In case of employment, the study finds that compared to illiterates, the chances of higher educated people going to agriculture sector is less. This is true even in the case of rural areas whereas the interactive variable (education with rural dummy) is found negatively associated with employment in agriculture sector. Occupation results suggest that there is a strong association between higher education (under graduate and graduate and above) with professional occupations and less with agriculture and fishery and unskilled occupations, suggesting the need for improving education and creating quality employment opportunities in the rural areas that may help in arresting the growing urban burden.
KerkoCite.ItemAlsoKnownAs: 10.1007/978-981-13-1414-8_8 2339240:22I8PCDJ 2405685:8FWZU7FX
Keywords: Education; Employment; India; Occupation; Urban-rural gap; Wages

Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) - Haßler, Björn; Brugha, Meaghan; Muyoya, Chisenga; Mitchell, Joel; Hollow, David; Jackson, Alan (Jigsaw and Open Develoment & Education, 2018)
Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) Also available at https://digitalprinciples.org/resource/donor-organizations-the-principles-for-digital-development-a-landscape-assessment-and-gap-analysis/, https://digitalprinciples.org/wp-content/uploads/PDD2018_interactive.pdf
EdTechHub.Source: 2129771:I2CG3TP3 shortDOI: 10/ghgk6z KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1204703 10/ghgk6z 2129771:I2CG3TP3 2129771:SI7RBL6P 2405685:46SDL9HI
Keywords: _DOILIVE; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Child labour and school dropout in least-developed countries: empirical evidence from Lao PDR - Xayavong, Thidavong; Pholphirul, Piriya (International Journal of Education Economics and Development, 2018)
Even though topics related to child labour and school dropout have been studied worldwide, little attention has focused in the least-developed countries. This paper examines the impact of child labour on school dropout by using national representative data surveyed in the Lao PDR, which serves as a case study of a least-developed country. Using an average wage of children by province as an instrumental variable, findings indicate that child labour, especially with regard to girls, has a strong impact on driving school dropout. Parental educational attainment, particularly mother's education, seems to show a significant effect on reducing the probability of dropping out. Our evidence supports the need to provide free education programs that have not yet been established in least-developed countries such as the Lao PDR. At the very least, given limited government budgets, support can be targeted to help vulnerable groups and poor families.
0 citations (Crossref) [2024-04-29] Publisher: Inderscience Publishers KerkoCite.ItemAlsoKnownAs: 10.1504/IJEED.2018.091067 2339240:D8CWVP2S 2405685:MMP8E79V
Keywords: Lao PDR; child labour; least-developed countries; school dropout; ⛔ No INSPIRE recid found

Building an online community: student teachers' perceptions on the advantages of using social networking services in a teacher education program - Habibi, Akhmad; Mukinin, Amirul; Riyanto, Yatim; Prasohjo, Lantip Diat; Sulistiyo, Urip; Sofwan, Muhammad; Saudagar, Ferdiaz (Turkish Online Journal of Distance Education, 2018)
This inquiry examined student teachers' perceptions on the advantages of using Social Networking Services (SNS) in an English teacher education program at a public university in Jambi, Indonesia to ease the communication, supervision, discussion, and report submissions between supervisors and student teachers. The networking types included in the program are Whatsapp, Telegram, Email, and Google Form. The method of the research was qualitative through using focus group discussions as the technique of collecting data involving forty-two student teachers. We organized our analysis and discussion around their perceptions and the contexts in which the advantages they perceived emerge. The analyses of the texts revealed that two salient themes with their sub-themes related to the advantages of using Social Networking Services (SNS) in a teacher education program were social interaction (peer discussion and platform to interact with supervisors or lecturers) and learning motivation and experience supports (self-directed learning, promotes critical thinking, content engagement). Some pedagogical and social implications are also discussed.
Publisher: Anadolu University, Office of the Rector, Eskisehir, 26470, Turkey Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2013525781?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.17718/tojde.382663 2405685:J6BE7A45 2534378:E9ZSB7L9 2534378:MCTX9ZFS
Keywords: Case Studies; College Students; Computer Mediated Communication; Critical Thinking; Data Analysis; ERIC; Current Index to Journals in Education (CIJE); Educational Benefits; Focus Groups; Foreign Countries; Group Discussion; Higher Education; Independent Study; Indonesia; Interpersonal Communication; Learner Engagement; Learning Motivation; Practicums; Preservice Teacher Education; Qualitative Research; Social Networks; Student Teacher Attitudes; Teacher Education Programs; __:import:01; __:match:final; __:matched; __:study_id:2097353; __finaldtb

Building an online community: student teachers' perceptions on the advantages of using social networking services in a teacher education program - Habibi, Akhmad; Mukinin, Amirul; Riyanto, Yatim; Prasohjo, Lantip Diat; Sulistiyo, Urip; Sofwan, Muhammad; Saudagar, Ferdiaz (Turkish Online Journal of Distance Education, 2018)
This inquiry examined student teachers' perceptions on the advantages of using Social Networking Services (SNS) in an English teacher education program at a public university in Jambi, Indonesia to ease the communication, supervision, discussion, and report submissions between supervisors and student teachers. The networking types included in the program are Whatsapp, Telegram, Email, and Google Form. The method of the research was qualitative through using focus group discussions as the technique of collecting data involving forty-two student teachers. We organized our analysis and discussion around their perceptions and the contexts in which the advantages they perceived emerge. The analyses of the texts revealed that two salient themes with their sub-themes related to the advantages of using Social Networking Services (SNS) in a teacher education program were social interaction (peer discussion and platform to interact with supervisors or lecturers) and learning motivation and experience supports (self-directed learning, promotes critical thinking, content engagement). Some pedagogical and social implications are also discussed.
Publisher: Anadolu University, Office of the Rector, Eskisehir, 26470, Turkey Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2013525781?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.17718/tojde.382663 2339240:76QI6ABS 2405685:27N3HDGU 2534378:E9ZSB7L9 2534378:MCTX9ZFS
Keywords: Case Studies; College Students; Computer Mediated Communication; Critical Thinking; Data Analysis; ERIC; Current Index to Journals in Education (CIJE); Educational Benefits; Focus Groups; Foreign Countries; Group Discussion; Higher Education; Independent Study; Indonesia; Interpersonal Communication; Learner Engagement; Learning Motivation; Practicums; Preservice Teacher Education; Qualitative Research; Social Networks; Student Teacher Attitudes; Teacher Education Programs; __:import:01; __:match:final; __:matched; __:study_id:2097353; __finaldtb

Short message service (SMS)–based remote support and teacher retention of training gains in Malawi - Slade, Timothy S.; Kipp, Scott; Cummings, Stirling; Nyirongo, Kondwani (Cultivating dynamic educators: case studies in teacher behavior change in Africa and Asia, 2018)
This book responds to growing recognition by international education professionals, policy makers, and funding partners of the need for qualified teachers and interest in the subject of teacher professional development (also referred to as "teacher behavior change"). The book responds to important questions that are fundamental to improving teaching quality by influencing teaching practice. These questions include: How do we provide high-quality training at scale? How do we ensure that training transfers to change in practice? What methods are most cost-effective? How do we know what works? The book includes case studies describing different approaches to teacher behavior change and illustrates how specific implementation choices were made for each context. Individual chapters document lessons learned as well as methodologies used for discerning lessons. The key conclusion is that no single effort is enough on its own; teacher behavior change requires a system-wide view and concerted, coordinated inputs from a range of stakeholders. This book contains the following chapters: (1) Understanding and Influencing Teacher Behavior Change: Editorial Introduction (Sarah Pouezevara); (2) Changing Teacher Educators' Conceptions and Practices Around Literacy Instruction: Lessons from Teacher Educators' Professional Development Experiences in Ethiopia (Dawit Mekonnen, Marion Fesmire, Adrienne Barnes, Stephen Backman, and Flavia Ramos-Mattoussi); (3) School Leadership and Early Grade Reading: Examining the Evidence in Zambia (Mitchell Rakusin and Guy Bostock); (4) Making Sense of Teacher In-Service Training in the Philippines (Nancy Clark-Chiarelli and Bonita Cabiles); (5) Short Message Service (SMS)-Based Remote Support and Teacher Retention of Training Gains in Malawi (Timothy S. Slade, Scott Kipp, Stirling Cummings, and Kondwani Nyirongo); (6) Relationships Between Coach Support and Teachers' Adoption of New Instructional Practices: Findings from the Nigeria Reading and Access Research Activity (RARA) (Karon Harden, Alison Pflepsen, and Simon King); (7) Using Activity Theory to Understand Teacher Peer Learning in Indonesia (Sarah Pouezevara, Feiny Sentosa, and Tifa Asrianti); (8) Teacher Motivation and Behavior Change: Results of the Teacher Motivation Diagnostic Tool in Northern India (Molly Hamm-RodrÃguez, Emily Richardson, and Jarret Guajardo); and (9) Once More Up the Mountain: The Promise of High-Quality Teaching Depends on Behavior Change (Lee E. Nordstrum). Contains a section about the contributors and an index. (Individual chapters contain references.) [Erin Newton compiled this volume.]
Publisher: ERIC KerkoCite.ItemAlsoKnownAs: 2339240:2M2HXSJN 2405685:SNDDADWB 2405685:SNTV94NA 2534378:7FFHYISA 2534378:ASX6DAFV 2534378:WH9M9DZM
Keywords: __:import:02; __:match:final; __:matched; __:study_id:3123693; __finaldtb; ⛔ No DOI found

Teaching Practices in the 21st Century in Kenya: A Qualitative Approach - Kaume-Mwinzi, Regina K. (International Journal of Educational Excellence, 2018)
Education is an engine for the growth and progress of any society and it is responsible for building human capital which sets technological and economic growth. In the pre-technology education context, the teacher controlled the instructional process, the content was delivered to the entire class and the teacher emphasized factual knowledge. However, the current global demands in education require the use of approaches that are learner-centered and embracing integration of ICT. The purpose of this study is to establish the pedagogy used in Kenya for the 21st century learner. The case study design was used to collect qualitative data from three teachers who were purposively sampled from three education sub-sectors in Kenya: primary, secondary and university. The interview was guided by three research questions: Which teaching practices are used in Kenya? Which are the ‘best’ teaching practices in Kenya in the 21st century? What are the barriers for the ‘best’ teaching practices in Kenya? The findings were that the teaching methods currently in use were mainly teacher-centered although the respondents revealed that the ‘best’ teaching practices for the 21st century learner were student-centered. However, the barriers were large classes, lack of resources and facilities among other factors. The study recommends realignment of education policies to give priority to build pedagogical capabilities of teachers, provide digital tools and other resources. This would enable the 21st century learners’ opportunity to unleash their potential.
KerkoCite.ItemAlsoKnownAs: 10.18562/ijee.034 10/ggjrhq 2339240:T76TEDIL 2405685:XJKPKRMP

The specific skills required of teachers who deliver K–12 distance education courses by synchronous videoconference: implications for training and professional development - Rehn, Nicki; Maor, Dorit; McConney, Andrew (Technology, Pedagogy and Education, 2018)
The purpose of this research is to identify the specific skills required of videoconference teachers who teach K–12 distance education courses. Many schools and educational districts worldwide are using videoconference technology to deliver courses to students as an economic solution when they cannot afford specialised teachers at remote locations. However, teachers are rarely trained to use this instructional technology and must therefore translate their experience in face-to-face and/or online teaching to this alternative medium. The collective case study used observations and interviews of eight teachers across five schools to identify the specific skills required to teach in a way that they perceived as successful in a videoconference class. It was found that teachers are largely under-prepared with strategies to project presence, develop relationships, foster interaction, manage the course and teach content across a distance when the screen is the main tool of connection. The authors offer a path to improvement that involves supporting teacher action research, creating communities of inquiry and developing teaching quality standards specific to videoconference.
Publisher: Routledge KerkoCite.ItemAlsoKnownAs: 10.1080/1475939X.2018.1483265 2405685:FP425A4V
Keywords: K–12; Videoconferencing; distance education; instructional technology; teacher roles

Applying the information search process model to analyze aspects in the design of serious games for children with hearing impairment - Cano, Sandra; Alghazzawi, Daniyal M.; Arteaga, Jaime Muñoz; Fardoun, Habib M.; Collazos, César A.; Amador, Viviana Bustos (Universal Access in the Information Society, 2018)
Deaf children traditionally face greater challenges and encounter difficulties particular to their abilities. The Information Search Process model (ISP) is oriented in the context of the present work as a process of searching for information about children with a hearing impairment in the area of literacy, applying the different stages of the ISP model to identify different aspects of hearing impairment. A case study was carried out at the USAER school in Aguascalientes, Mexico, a school that enables children with hearing impairments to be included in regular secondary schooling. The children here are aged 12–15 years and have literacy problems. Eight children from 7 to 11 years of age were also evaluated in the Institute for Deaf and Blind Children in Cali, Colombia. The ISP model can be deemed to have been useful for identifying the relevant needs to support both teachers and deaf children. A need was identified, to construct a game that integrates the activities undertaken following the FitzGerald keys and in turn allow them to assess learning through different activities that help increase the semantic repertoire.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10209-016-0520-x 2339240:UHUF6RAC 2405685:FBY7T8A3

Leaving no-one behind: Improving climate change and entrepreneurship education in sub-Saharan Africa through E-learning and innovative governance systems - Chirambo, Dumisani (Climate Literacy and Innovations in Climate Change Education: Distance Learning for Sustainable Development, 2018)
Poverty and climate change vulnerability is increasing in Sub-Saharan Africa (SSA) because the region lacks education and skills development facilities, and sustainable governance systems. Arguably, mainstreaming climate literacy in secondary schools through Information and Communications Technology (ICT) modalities can promote sustainable development and climate change resilience by providing early opportunities for the youth to gain knowledge and awareness of the behavioral and cultural changes that may foster improved climate change resilience. Through an inductive analysis based on research articles, case studies, policy briefs, and academic literature reviews, this chapter sought to highlight emerging ICT learning contexts in SSA as a means to determine the extent to which ICT may be used to promote climate change and sustainable development education in secondary schools. The chapter showed that climate literacy at secondary schools was being constrained by a lack of climate change education material and content on existing ICT learning platforms; and a lack of innovative governance systems to support governments in delivering climate literacy content to secondary schools and the youth. Consequently, to “leave no-one behind” requires non-state actors to develop and utilise innovative governance systems and digital climate literacy material that can complement government efforts to mainstream climate literacy at secondary schools.
KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-319-70199-8_3 2339240:3KUJPMJY 2405685:RMVKCCC3

“Matching Person & Technology (MPT) Model” for Technology Selection as Well as Determination of Usability and Benefit from Use - Martinez, A. P.; Scherer, M. J. (Living in the State of Stuck, 2018)
Technologies have become smarter, smaller, more portable or wearable, and more adaptable. This has led to more choice and, in many cases, complexity in decision-making about selecting the best device and features for a given user. A good match of person and technology requires attention to (a) aspects of and resources in the environments in which the technology will be used, (b) the needs, expectations and preferences of the user, and (c) the functions and features of the technology and service delivery process. If the match is not a quality one from the standpoint of the end user, and the user experience (UX) is not satisfactory, then the technology may go unused, or may not be used optimally. There is a need for an improved person-AT matching and outcomes assessment process because studies and reports show in general that there is a high level of dissatisfaction and nonuse or discard of technology by consumers. Psychologists are uniquely qualified to partner with technology developers in implementing an assessment process that inquires into the potential technology user's predisposition to use a particular technology by addressing, subjective view of current capabilities, view of achievements as well as needs in key life domains of activities and participation, and ratings of fundamental personal factors such as mood status, support from others, engagement in therapy activities and desire to use technology. Utilization of the MPT model and accompanying assessment process has been proven to result in enhanced technology use and goal achievement. Research increasingly highlights the fact that consumers are less likely to use recommended devices when their needs are neither fully addressed nor understood during the technology selection process. A user's perspective of their needs and preferences may be obtained by having them identify and prioritize their desired outcomes and then rate progress in achieving them. This approach was used in developing the Matching Person and Technology measures and has also been used in developing Such a person-centered approach allows outcomes to be measured in reference to changes in a person's satisfaction in achieving desired goals, not merely their functional ability to achieve them. An idiographic evaluation is used (i.e., the person is the unit of analysis and serves as his or her own control), not a normative one (i.e., the person is compared to his or her peers). An idiographic evaluation best captures a consumer-directed and social model perspective of outcomes assessment. Many studies have examined the psychometric qualities and usefulness of the Matching Person and Technology measures. Below is the most recent data on one MPT measure, the Assistive Technology Device Predisposition Assessment (ATD PA), from a study done in the country Greece (Koumpouros et al. 2017; n=115).  Excellent interrater reliability (ICC=0.981, ranging from 0.973-0.987)  Adequate internal consistency (Cronbach's alpha =0.701, ranging from 0.605-0.701)  Adequate-Excellent construct validity for items in the Adaptablility subscale (r=0.537 to 0.783)  Excellent construct validity for items in the Fit to Use subscale (r= 0.691 to 0.801)  Adequate-Excellent construct validity for items in the Socializing (r= 0.498 to 0.767)  Low correlation coefficients between each subscale, indicating subscales measure unique constructs Improvements in person-centered assistive technology services and outcomes assessment are needed, given reports of a high level of dissatisfaction and nonuse of technology by consumers. It is important to ensure an evidence-based, client-centered assessment for determining the match of individuals with the most appropriate technologies for their use. Achieving a desired outcome begins at the point of technology consideration and then progresses to product selection. ABSTRACT Cognitive impairment often results in a range of functional and lifestyle changes for many individuals. This article discusses the development and evolution of a multidisciplinary model of cognitive rehabilitation outpatient practice that integrates technology to improve patient outcomes. The described interdisciplinary treatment approach highlights the need for collaboration by treating providers; focuses on the individual being an active participant in treatment; and discusses the value that assistive technology can bring to cognitive rehabilitation work as it relates to patient success, functional improvement, and implementation of appropriate and patient specific technological strategies.
KerkoCite.ItemAlsoKnownAs: 10.13140/RG.2.2.23218.50889 2339240:93CVYV3N 2405685:G8RXEBKN

Sustaining and scaling pedagogic innovation in sub-Saharan Africa: Grounded insights for teacher professional development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this concept paper we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our experiences of over 5 years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. “OER4Schools” integrates interactive pedagogy, Open Educational Resources (OER) and use of mobile devices (where available). The focus of this paper is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through use of OER. Our conclusions thereby offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for programme design and implementation, that should be taken on board by future initiatives.
00000 EdTechHub.Source: 2129771:D2GQYC5S KerkoCite.ItemAlsoKnownAs: 10.56059/jl4d.v5i1.264 2129771:43ZT3XWL 2129771:52KKAHKR 2129771:AAT7FR3H 2129771:D2GQYC5S 2129771:LDWSNI7T 2129771:LHMXV7QF 2249382:CS9PALG8 2317526:6IH7CD39 2317526:PP4CHVEG 2339240:2BCABLG6 2339240:4N3G4XDJ 2339240:9BPXVI62 2339240:C7CKIPL7 2339240:D83N6FTA 2339240:HGHAYJ5G 2339240:HR2YGWX3 2339240:P65I7MGU 2339240:YSVITTWH 2405685:3GSCKVWC 2405685:7X2D9JDG 2405685:CUHYHFLV 2405685:M8UDHT7A 2405685:NKSYKNQN 2405685:NVEVT9HX 2405685:NZ3GKZCR 2405685:T2I86FZT 2405685:ZFJ79LQS 2486141:Z3PRLX4K 257089:AJJPQKDF 261451:JC3NQMN3 261495:BWD9L8FL 261495:TCP47GGI
Keywords: AWP2; Active Learning; Africa; Author:Haßler; C:sub-Saharan Africa; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; Teacher Professional Development; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; dode_eth-src-dode; dode_eth-trf2-dode; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa; ⛔ No DOI found

School leadership and early grade reading: Examining the evidence in Zambia - Rakusin, M; Bostock (Cultivating Dynamic Educators: Case Studies in Teacher Behavior Change in Africa and Asia. RTI Press Publication BK-0022-1809., 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:4DM4ULGQ 2405685:R2HB5B8Z